A Framework to study Antifragility for Enterprise Risk Management: Case Study of Unconventional Oil and Gas Operations in Latin America (2021)
This research builds on the most recent organizational resilience theories to elaborate heuristic tests to prove the antifragility concept, the last defined step for companies to cope with VUCA (Volatile, Uncertain, Complex, and Ambiguous). Given its novelty, the body of knowledge regarding antifragility is weak. There are only a few definitions and attributes to describe antifragility at the organizational level and a total absence of real firm cases, theory, and hypotheses research. The antifragility concept offers new management and risk assessment tools to organizations eager to survive and take advantage of the new opportunities that unfold behind the threat of uncertainty. Antifragility goes beyond business continuity and resilience by focusing on the firms' ability to deliver products and services at acceptable levels after a disruptive event and taking advantage of the upside risk involved in uncertainty to improve performance and foster innovation and growth. This study's main contribution is defining proper metrics to identify and rank the organizational resilience level after an extreme event and define a framework to describe the selected antifragile companies' common attributes and competencies. The results from this study will serve as the basis for organizations that struggle to operate in VUCA and are exposed to surprising, extreme events, also known as Black Swans. Additionally, the proposed antifragility framework and measurement system will also strengthen the risk assessment and management disciplines.